Using electromagnetic induction to inform precision turfgrass management strategies in sand‐capped golf course fairways - Dallas M. Williams; Chase M. Straw; A. Peyton Smith; Kathryn L. Watkins; Sarah G. Hong; Weston F. Floyd; Briana M. Wyatt (Agrosystems, Geosciences & Environment)
Abstract To meet the turfgrass standards that players expect, golf course superintendents rely on intense irrigation, fertilization, and cultivation programs. However, the overapplication of irrigation water and fertilizer has been shown to have negative effects on water quality. Precision turfgrass management (PTM) is an emerging area of interest as more golf course superintendents are looking to increase input efficiency while simultaneously reducing water and fertilizer input costs, as well as environmental impacts. Our objectives were to (1) use electromagnetic induction (EMI) to determine the spatial variability of apparent electrical conductivity (EC) in sand‐capped fairways and (2) correlate EC to measured soil and turfgrass characteristics to determine the applicability of mapping EC for PTM. Soil samples and EC data were collected in spring 2021 on four sand‐capped fairways from two golf courses (one hybrid bermudagrass and one zoysiagrass) belonging to the same facility in southeast Texas. Apparent EC was found to be positively and significantly correlated with soil volumetric water content (VWC, 0.40 < r > 0.62) and turfgrass normalized difference vegetation index (NDVI; 0.21 < r > 0.46) in three of four fairways, while EC was negatively and significantly correlated with penetration resistance (PR, −0.29 < r > −0.48) in two of four fairways studied. The strengths of these relationships were corroborated by strong visual similarities when comparing spatial maps of EC with those of VWC, NDVI, and PR, indicating that EMI‐based EC data have potential for use in delineating site‐specific management zones for water and fertilizer applications, as well as targeted aeration.